Political Labeling on Social Media: a Netnographic Study of “SDM Rendah” in Indonesia’s 2024 Presidential Election on X (Twitter) - Ruth Novarefie Putri Paath; Azzahra Qubais Suprapto; Hayunaji Hayunaji; Muhammad Edi Irfandianto (Green Publisher Indonesia, 2024)
The 2024 presidential election campaign in Indonesia has produced various unique phenomena, including the emergence of the